2016
DOI: 10.1136/bmjopen-2015-009857
|View full text |Cite
|
Sign up to set email alerts
|

Does preoperative rehabilitation for patients planning to undergo joint replacement surgery improve outcomes? A systematic review and meta-analysis of randomised controlled trials

Abstract: ObjectivesThe clinical impact of preoperative physiotherapy on recovery after joint replacement remains controversial. This systematic review aimed to assess the clinical impact of prehabilitation before joint replacement.DesignWe searched PubMed, Embase and Cochrane CENTRAL up to November 2015 for randomised controlled trials comparing prehabilitation versus no prehabilitation before joint replacement surgery. Postoperative pain and function scores were converted to Western Ontario and McMaster Universities O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
141
2
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(155 citation statements)
references
References 60 publications
6
141
2
6
Order By: Relevance
“…Pre‐operative rehabilitation interventions (or “prehabilitation”) for the purposes of improving post‐operative recovery have received considerable interest. Our search identified nine systematic reviews including 14 randomised trials. Interventions included a heterogeneous group of exercise programs, including physiotherapist supervised and unsupervised exercise, coupled with co‐interventions including acupuncture, kinesiology and education .…”
Section: Optimising Pre‐operative Status To Maximise Recovery and Attmentioning
confidence: 99%
See 2 more Smart Citations
“…Pre‐operative rehabilitation interventions (or “prehabilitation”) for the purposes of improving post‐operative recovery have received considerable interest. Our search identified nine systematic reviews including 14 randomised trials. Interventions included a heterogeneous group of exercise programs, including physiotherapist supervised and unsupervised exercise, coupled with co‐interventions including acupuncture, kinesiology and education .…”
Section: Optimising Pre‐operative Status To Maximise Recovery and Attmentioning
confidence: 99%
“…Our search identified nine systematic reviews including 14 randomised trials. Interventions included a heterogeneous group of exercise programs, including physiotherapist supervised and unsupervised exercise, coupled with co‐interventions including acupuncture, kinesiology and education . While two reviews found marginal benefits to length of stay and knee range of motion, and one review demonstrated a dose–response benefit to several physical outcome measures, there was little benefit when a GRADE (Grading of Recommendations Assessment, Development and Evaluation) assessment of the evidence was performed .…”
Section: Optimising Pre‐operative Status To Maximise Recovery and Attmentioning
confidence: 99%
See 1 more Smart Citation
“…However, low pre-operative function is a significant risk factor for increased LOS and predictive of worse longer-term function (Biring et al, 2007;Davis et al, 2006;Yeung et al, 2010). There are no studies of rehabilitation before RTHR but there is some evidence that exercise can improve pain, muscle strength and function before primary THR (Gill & McBurney, 2013;Skoffer, Dalgas, & Mechlenburg, 2015;Wang et al, 2016) although the size and clinical importance of these changes is debated. Whether pre-operative rehabilitation focused on optimizing function before RTHR is safe, feasible and can improve outcomes seems relevant to investigate.…”
Section: Pre-operative Carementioning
confidence: 99%
“…Una revisión sistemática y metaanálisis pone de manifiesto que los beneficios son modestos y clínicamente no relevantes (104).  Elevaciones periódicas de la extremidad inferior intervenida.…”
Section: Movilización Precoz Rehabilitación Postquirúrgicaunclassified